Using 3D game engines and GPU for ray launching based channel modeling in indoor (2014)
This paper investigates the use of a full 3D ray-launching system based on Game Engine and GPU for the prediction of channel parameters in indoor. We explore the behavior of the materials and the possible influence of objects external to the room where measurements were performed. We explore the modeling of indoor channel for Digital TV frequencies and analyze the behavior of material on such low frequencies and how the frequencies affect the constitutive parameters of materials in the scenario. Because of the environment used for experimentation, the number of rays is very high and the number of interactions is higher than usual. We show results of the ray tracing model compared with measurements of delay spread at 594MHz in a meeting room